2010
DOI: 10.1111/j.1346-8138.2010.00872.x
|View full text |Cite
|
Sign up to set email alerts
|

Hair transplantation for therapy‐resistant alopecia areata of the eyebrows: Is it the right choice?

Abstract: Alopecia areata is a common skin disorder of presumed autoimmune etiology and it usually shows an unpredictable course. Treatment of alopecia areata is challenging. There is very little information on the use of surgical therapies for the treatment of alopecia areata in the medical published work. A 24-year-old male patient was referred to a private hair transplantation clinic owned by one of the authors for the treatment of therapy-resistant alopecia areata affecting both eyebrows. He had quickly lost all bod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…4 Civas et al, in 2010, reported HT in AA of eyebrow. 6 They did not give any other oral or topical immunosuppressant to their patient post-FUE. They attribute the sustainability of their grafts to the addition of triamcinolone acetonide during tumescent anesthesia while performing FUE.…”
Section: Discussionmentioning
confidence: 99%
“…4 Civas et al, in 2010, reported HT in AA of eyebrow. 6 They did not give any other oral or topical immunosuppressant to their patient post-FUE. They attribute the sustainability of their grafts to the addition of triamcinolone acetonide during tumescent anesthesia while performing FUE.…”
Section: Discussionmentioning
confidence: 99%
“…Prior to this, a few reports have described the use of HT to treat stable areas of AA resistant to medical treatment. [2][3][4] Results are mixed but largely report at least initial success. In a report by Barankin et al, 2 a patient with persistent steroid resistant AA over the eyebrow managed to maintain hair growth for 8 months after HT from the scalp.…”
Section: Discussionmentioning
confidence: 99%
“…Although AA subsequently relapsed, it was now responsive to monthly triamcinolone injections. In another report by Civaş et al, 3 occipital hairs were transplanted into an alopecic area that had been stable for 18 months. The patient did not receive topical or systemic therapies for AA postoperatively, and hair regrowth was 80% by 2 years.…”
Section: Discussionmentioning
confidence: 99%
“…A few treatment modalities are available for treating AA, but none are curative or preventive . Pre‐existing treatment modalities of AA or hair transplantation have been used to treat AA of the eyebrow . In addition, medications known to be effective in eyebrow hypotrichosis, such as 2% minoxidil or bimatoprost, have also been used; however, such treatments have demonstrated unclear efficacy .…”
Section: Introductionmentioning
confidence: 99%